DEVELOPMENT OF TEACHING INDUSTRY MODEL IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN VOCATIONAL HIGH SCHOOLS - Fitrah Asma Darmawan; Purnamawati Purnamawati; Mustamin Mustamin; Fauziyyah Alimuddin (Lembaga Penelitian Mahasiswa Penalaran UNM, 2024)
This study aims to produce a Teaching Industry-based (TI-based) learning model in accordance with the characteristics of Independent Curriculum (IC) in Vocational High Schools (VHS) and produce an TI-based learning modules for implementation of learning in accordance with IC in VHS. This study is a research & development that follows the development model of Plomp (2007), which starts from initial investigation, model testing, and model implementation. Yet, in the initial stage, this study focuses on the design of TI-based learning model and the development of TI-based learning modules that are in accordance with the characteristics of IC. The model development procedure starts with study of the teaching industry theories, the learning models theories that are relevant to the TI concept, and the independent curriculum concept. Furthermore, the syntax of TI-based model in the context of IC is adopted and elaborated from learning syntaxes relevant to the TI concept. The learning module developed starts from the step of analyzing learning objectives and work competencies that must be mastered by students (hard skills and soft skills). Furthermore, the module was tested on users with 45 respondents. The data were analyzed using quantitative descriptive analysis techniques to describe the feasibility of the learning module.